Endoscopic Management of Gastric Varices: Efficacy and Outcomes of Gluing with N-Butyl-2-Cyanoacrylate in a North American Patient Population - PJ Belletrutti; J Romagnuolo; RJ Hilsden; F Chen; B Kaplan; J Love; PL Beck (Canadian Journal of Gastroenterology)
BACKGROUND: Gastric variceal bleeding is associated with significant morbidity and mortality in patients with portal hypertension. Outside of North America, gastric variceal injection of N-butyl-2-cyanoacrylate has been shown to be safe and effective. The majority of studies on this mode of therapy are in Asian populations in which the etiology of portal hypertension differs from North America.